The Association of Occipital Spur with Craniocervical Posture and Craniofacial Morphology - Cheng Q; Xiao C; Lau Rui Han S; Hu S; Wu X; Dong Y; Xiong X; Fang S (Journal of Pain Research)
Qiaoyu Cheng,1 Chuqiao Xiao,1 Sophie Lau Rui Han,1 Shoushan Hu,1 Xiayanran Wu,1 Yanhua Dong,1 Xin Xiong,1 Shanbao Fang2 1State Key Laboratory of Oral Diseases & National Center for Stomatology & National Clinical Research Center for Oral Diseases, West China Hospital of Stomatology, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 2Department of Orthodontics, College & Hospital of Stomatology, Guangxi Medical University, Nanning, Guangxi, 530021, People’s Republic of ChinaCorrespondence: Xin Xiong, State Key Laboratory of Oral Diseases & National Center for Stomatology & National Clinical Research Center for Oral Diseases, West China Hospital of Stomatology, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China, Email drxiongxin@scu.edu.cn Shanbao Fang, Department of Orthodontics, College & Hospital of Stomatology, Guangxi Medical University, Nanning, Guangxi, 530021, People’s Republic of China, Email fangshanbao@gxmu.edu.cnPurpose: This cross-sectional study aimed to evaluate the relationship between occipital spur (OS) with both craniocervical posture and craniofacial morphology.Methods: The study involved 240 lateral cephalograms from subjects with and without OS. The craniocervical posture and facial morphology of every individual were assessed through Uceph software analysis of their cephalograms, considering 32 variables. The Independent T-test and the Mann–Whitney U-test were used to evaluate the relationships between the measures and OS. Differences in craniocervical posture and craniofacial morphology between the two groups were investigated by logistic regression.Results: Subjects with OS exhibited more severe forward head posture (FHP) (larger C0-C1, Ba-C3ia, C2ap-C4ip, craniocervical angle, CVT-OPT, and NSL-C2’) and larger facial configuration (greater mandibular body length, posterior cranial base length, and posterior facial height) than the subjects without OS. Larger C2ap-C4ip (OR 1.53; 95% CI 1.282~1.82), Craniocervical angle (OR 1.70; 95% CI 1.457~1.977) and NSL-C2’ (OR 1.18; 95% CI 1.097~1.264), were associated with greater likelihood of having OS.Conclusion: The subjects with OS were more prone to forward head posture than the control group. For subjects observed with OS on cephalograms, attention should be given to their possible abnormal cervical and head postures.Keywords: occipital spur, craniocervical posture, craniofacial morphology, cephalometric analysis, forward head posture